2014
DOI: 10.1364/ol.39.006791
|View full text |Cite
|
Sign up to set email alerts
|

Airy beams generated by ultrafast laser-imprinted space-variant nanostructures in glass

Abstract: We demonstrate a technique to generate accelerating Airy beams with a femtosecond laser-imprinted space variant birefringent structure in silica glass. Our approach enables the generation of dual Airy beams with polarization sensitive beam deflection. The produced beam is used for the glass scribing. After the glass-breaking process, a spontaneous self-detachment of a fiber-like structure occurs that can be exploited as an alternative way for fabricating glass cantilevers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…12 It has been demonstrated that materials irradiated with femtosecond laser pulses undergo the self-assembly process, which results in nanostructures produced on the surface 13,14 or inside the material. 15,16 Recently, this technology was harnessed for producing a series of birefringent optical elements inside silica glass, 12,[17][18][19] while the optical anisotropy produced by laser-induced periodic surface structures (LIPSS) has not been reported. However, as the form birefringence depends on the refractive index modulation, 1 the amount of form birefringence achieved in nanostructured silica glass 20 is of the order of natural birefringence found in crystalline materials such as quartz.…”
mentioning
confidence: 99%
“…12 It has been demonstrated that materials irradiated with femtosecond laser pulses undergo the self-assembly process, which results in nanostructures produced on the surface 13,14 or inside the material. 15,16 Recently, this technology was harnessed for producing a series of birefringent optical elements inside silica glass, 12,[17][18][19] while the optical anisotropy produced by laser-induced periodic surface structures (LIPSS) has not been reported. However, as the form birefringence depends on the refractive index modulation, 1 the amount of form birefringence achieved in nanostructured silica glass 20 is of the order of natural birefringence found in crystalline materials such as quartz.…”
mentioning
confidence: 99%
“…In this case the phase factor in the output field depends on the optical length, which is purely dynamic in nature. More recently, a simple and effective way of generating Airy beams based on the geometric phase element is proposed [15]. A dielectric metasurface based on laser-induced nanogratings in fused silica-glass works as a space-variant phase element to produce the Airy phase.…”
mentioning
confidence: 99%
“…The filtering scheme consists of widely available components, is simple to implement and can be extended to any optical element based on the phase control of circularly polarized light, e.g. q-plates, not only as optical vortex converter but also as, e.g., Airy beam converter [40]. The demonstrated wavelength range spans over 600 nm over the VIS and nIR range with the efficiency of filtering higher than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, even if any S-Waveplate or, in general, any other optical element based on the phase control of circularly polarized light by half-wave plates (e.g. [40]) is designed for a specific wavelength, a desired transformed part of the beam can be easily separated out using a circular polarizer.…”
Section: A Theorymentioning
confidence: 99%